Comparison of the O’Brien Filter Test and the PFA-100 Platelet Analyzer in the Laboratory Diagnosis of von Willebrand’s Disease - Schlammadinger, Agota; Kerenyi, Adrienne; Muszbek, Laszlo; Boda, Zoltan (Thrombosis and Haemostasis, 2000)
Von Willebrand’s disease (vWD) is the most common congenital haemorrhagic diathesis, characterized by the quantitative or qualitative disorder of von Willebrand factor (vWF). A number of methods have been used for the diagnosis of the disease, and the bleeding time determination is widely accepted as a screening test in spite of its low sensitivity. Our aim was to evaluate and compare the performance of two high shear systems (the O’Brien filter test and the PFA-100 device) in the screening and diagnosis of vWD. Thirty patients (n=13 type 1 with mild symptoms, n = 9 type 1 with severe symptoms, n = 2 type 2A, n = 3 type 2B and n = 3 type 3 vWD) and twenty controls were investigated. In mild vWD the platelet retention in the second phase of the filter test with citrated blood showed the highest sensitivity (91.6%). The sensitivity of the PFA-100 method with collagen-epinephrine cartridges in this group was 76.9%, while the bleeding time was prolonged only in 15.4% of the cases. In severe type 1, in type 2A and type 3 all functional tests reflected the bleeding tendency of the patients. In type 2B disease the bleeding time was prolonged only when the patient was thrombocytopenic, but both high shear systems revealed the disease independently of the presence of thrombocytopenia. The overall sensitivity of the bleeding time determination was 50% compared to the 80-90% sensitivity of the O’Brien filter test and the PFA-100 system. The sensitivity values of the filter test and the PFA-100 device with collagen-epinephrine cartridges were in the same range, but the collagen-ADP cartridges showed a lower (65.5%) sensitivity, though the results were specific and had high positive predictive value. We conclude that both high shear systems are suitable for the screening of vWD, and that they are superior to the traditional bleeding time determination in case of mild disease or type 2B vWD.
Keywords: von Willebrand’s disease; high shear induced platelet activation; O’Brien filter test; PFA-100 system